Cloning of cDNA and the gene encoding human hepatocyte nuclear factor (HNF)-3β and mutation screening in Japanese subjects with maturity-onset diabetes of the young - Yamada, S.; Zhu, Q.; Aihara, Y.; Onda, H.; Zhang, Z.; Yu, L.; Jin, L.; Si, Y. -J.; Nishigori, H.; Tomura, H.; Inoue, I.; Morikawa, A.; et al. (Diabetologia, 2000)
Molecular defects of the genes for transcription factors, hepatocyte nuclear factor (HNF)-4 alpha, HNF-1 alpha, HNF-1 beta and insulin promoter factor-1 cause maturity-onset diabetes of the young (MODY1, 3, 5, and 4, respectively). This suggests the HNF-related transcription cascade is important in insulin secretion which is induced by glucose. These genes and the gene encoding glycolytic enzyme glucokinase (MODY2) are, however, responsible for only 15-20% of cases of MODY in the Japanese. Searching for a novel form of MODY in this population, we cloned a new candidate gene encoding human HNF-3 beta, a winged helix transcription factor, which also belongs to the same HNF-transcription cascade. The cDNA clone for human HNF-3 beta was isolated from a liver cDNA library. The gene was also cloned from a genomic library and its organization and chromosomal localization were determined. We screened 68 Japanese subjects with MODY/early-onset diabetes for mutations in this gene. Human HNF-3 beta is composed of 457 amino acids. The human gene, which was mapped to the segment 30 cR from SHGC-37039 on chromosome 20p by radiation hybrid mapping, spans approximately 4.5 kb and consists of three exons. Direct sequencing of the exons and flanking regions identified one missense mutation A328 V and seven polymorphisms, although the functional significance of the mutation in the pathogenesis of diabetes is not known. The characterization of the structure of the HNF-3 beta gene and its mapping in the framework of markers will be helpful in genetic studies of the various forms of diabetes mellitus.